Capsule Commentaries. - Hendrickson, Harvey S.; Gramling, Lawrence J.; McAllister, Leray L.; Brown, Richard E.; Roser, Sherman R.; Anderson, Matthew A.; Jensen, Daniel L. (The Accounting Review, 1986)
Abstract Reviews several books. "Secrets of the Tax Revolt," by James Ring Adams; "Financial Statement Analysis: Theory, Application, and Interpretation," 3rd ed., by Leopold A. Bernstein; "Perspectives in Auditing," 4th ed., by D.R. Carmichael and John J. Willingham; "Tax Shelter Alternatives: Measuring the Risks," by Michael N. Fitzerald.